1997
DOI: 10.1007/s001289900465
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pesticides in the Arno River and in Potable Water—A Survey of the Period 1992–1995

Abstract: The Arno river is one of the largest rivers in Italy. Its catchment area is approx. 8200 km 2 , where pesticides are extensively used for agricultural purpose. The pesticides used can enter the river by superficial runoff (Pereira and Rostad 1990;Thurman et al. 1991) precipitation and discharge of wastewater. Because more than 90 % of the raw water used for the public water supply of Florence comes from the Arno river, public concern has increased regarding pesticide contamination of drinking water, and one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 7 publications
0
15
0
3
Order By: Relevance
“…However, in this case, it could also be possible that organic carbon is not the only contributor to adsorption since some inorganic surfaces of the rock fragments could be responsible for adsorption, increasing the K oc value (Griffini et al, 1997;Kah and Brown, 2006;Aggarwal et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…However, in this case, it could also be possible that organic carbon is not the only contributor to adsorption since some inorganic surfaces of the rock fragments could be responsible for adsorption, increasing the K oc value (Griffini et al, 1997;Kah and Brown, 2006;Aggarwal et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Then, an appropriate amount of Fe 2+ in the range from 0 to 4 mM was added (as FeSO 4 ·7H 2 O) and the pH was adjusted to 3.5 ± 0.1 with sodium hydroxide or sulphuric acid. According to literature [37,38], this pH is in the optimum range of pH (3)(4) to promote the formation of HO • radicals in Fenton process, which has been verified by performing several experiments for pH ranges from 3 to 6, and it was found that 95-100% TOC removal was obtained in the pH range of 3-4. In all cases, the reaction was started by adding appropriate dose of H 2 O 2 (30%) to obtain concentrations of 2-20 mM H 2 O 2 in solution.…”
Section: Fenton Processmentioning
confidence: 68%
“…Fenton process is a promising and easy to manipulate advanced oxidation technology in which a mixture of hydrogen peroxide (H 2 O 2 ) and ferrous iron (Fe 2+ ) salts is added directly to the wastewater. This mixture promotes the formation of HO • radicals by catalytic decomposition of H 2 O 2 in acidic medium (pH in the range 3-4) as shown by the reactions sequence (1)(2)(3)(4)(5): …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Compared with the pesticides concentrations in European freshwaters, parathion methyl was detected in the Segre (Spain), Elbe and Rhine rivers (Germany) at concentrations up to 270, 332 ng/L and 40 ng/L, respectively (Planas et al 1997;Gotz et al 1998). Malathion was detected in River Arno (Italy), at 170.0 ng/L (Griffini et al 1997), and dimethoate in the Elbe and Rhine rivers (Germany) at 3,210.0 ng/L and 50.0 ng/L, respectively (Gotz et al 1998). The concentrations of the dimethoate, methyl parathion, and malathion in this study were much lower, which suggested that the Chinese surface water is also somewhat moderately polluted by dimethoate, methyl parathion, malathion, and parathion.…”
Section: Resultsmentioning
confidence: 95%